Soluções do tipo buraco-negro em teorias com violação da simetria de Lorentz gerada por campos tensoriais antissimétricos - Lessa, Leandro Alcântara (2020)
We study the gravitation effects on a static and spherically symmetric spacetime due to the vacuum expectation value (VEV) of a Kalb-Ramond field. The Kalb-Ramond VEV is a background tensor field which produces a local Lorentz symmetry breaking (LSB) of spacetime. Considering a non-minimal coupling between the Kalb-Ramond (VEV) and the Ricci tensor, we obtain an exact parameterdependent power-law modified black hole. For a particular choice of the LSB parameter, the Lorentz violation produces a solution similar to the Reissner- Nordstrom, despite the absence of charge. The near-horizon geometry is modified by including a new inner horizon and shifting the Schwarzschild horizon. Asymptotically, the usual Minkowski spacetime with a background tensor field is recovered. Analyzes of the stress-energy tensor to verify whether or not it violates the energy conditions were performed. By means of the Mercury perihelion test, an upper bound to the local Lorentz violation (LV) is obtained. In addition, other types of non-minimal couplings between Kalb-Ramond (VEV) and gravity were briefly analyzed.